Estrutura espacial de sistemas agroflorestais na paisagem rural de um município na Amazônia matogrossense - Paula, Rafael Pereira de (2019)
In this work, the spatial structure of agroforestry systems (AFS) is placed as a subject of study, with emphasis on the landscape of the municipality of Terra Nova do Norte-MT, belonging to the Amazonian biome. The objective was to analyze the spatial structure of the rural properties of the municipality and the AFS that compose them; characterize and analyze the spatial structure of the land cover and land use classes in a hydrographic basin in the municipality, relating them to the structure of AFS and natural vegetation; and propose alternatives that aim to improve and/or conserve aspects related to the ecology of the landscapes analyzed. Chapter 1 discusses the spatial structure of rural properties, and the AFS that compose them, in the rural landscape of the municipality. The structure of rural properties reflects a spatial organization that advocated access to water sources and roads, characteristic of colonization. The structure of AFS is related to its objective as production or restoration and its spatial distribution shows an inclination for the diversification of the productive matrix and concern with the restoration and preservation of water resources. Chapter 2 discusses the spatial structure of land cover and land use in a river basin in the municipality, addressing the role of AFS in increasing forest cover and compliance with environmental legislation in different scenarios. The hydrographic micro basin underwent intense fragmentation of the natural vegetation for the implantation of pastures. In this way, the AFS contribute to the improvement of the ecological characteristics of the landscape and are presented as an alternative for the restoration of the connectivity of the fragmented landscape.